2016
DOI: 10.1002/jbm.b.33778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyvinylidene fluoride electrospun fiber orientation on neural stem cell differentiation

Abstract: Electrospun polymer piezoelectric fibers can be used in neural tissue engineering (NTE) to mimic the physical, biological, and material properties of the native extracellular matrix. In this work, we have developed scaffolds based on polymer fiber architectures for application in NTE. To study the role of such three-dimensional scaffolds, a rotating drum collector was used for electrospinning poly(vinylidene) fluoride (PVDF) polymer at various rotation speeds. The morphology, orientation, polymorphism, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 80 publications
(277 reference statements)
1
81
0
4
Order By: Relevance
“…It has been previously shown that fibrous scaffolds promote neurite migration, and growth along the nanofiber orientation . Moreover, primates neurones exhibited elongated morphology parallel to the fibers direction when cultured on electrospun PVDF sheets . Interactions between PVDF and cells were extensively studied, particularly for bone tissue engineering .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that fibrous scaffolds promote neurite migration, and growth along the nanofiber orientation . Moreover, primates neurones exhibited elongated morphology parallel to the fibers direction when cultured on electrospun PVDF sheets . Interactions between PVDF and cells were extensively studied, particularly for bone tissue engineering .…”
Section: Resultsmentioning
confidence: 99%
“…[55,56] Moreover, primates neurones exhibited elongated morphology parallel to the fibers direction when cultured on electrospun PVDF sheets. [57] Interactions between PVDF and cells were extensively studied, particularly for bone tissue engineering. [29] It has been demonstrated that increased beta phase PVDF films favored fibronectin protein adsorption, and facilitated osteoblats adhesion and proliferation.…”
Section: Neonatal Rat Ventricular Myocytes Seeding and Cultivation Onmentioning
confidence: 99%
“…In the case of highly aligned fibers, cell elongation is highly parallel to the direction of fiber orientation, while it is random for nonorganized fibers . Lins et al selected the aligned and nonaligned fiber–based architectures to investigate their effects on the behavior of monkey NSCs ( Figure A,B) . They found that nonaligned electrospun polyvinylidene difluoride (PVDF) fibers were suitable for both glial differentiation and NSC maintenance, whereas aligned PVDF fibers were more suitable for neuronal differentiation.…”
Section: Effects Of Surface Properties On Cellular Behaviorsmentioning
confidence: 99%
“…14,15 It has also been reported that a certain degree of nanofiber alignment is important for specific bio-medical applications. [16][17][18] The combined role of polymer chemical structure and nanofiber alignment shows a significant effect in promoting interactions with cells, such as controlling the phenotype and morphology of osteoblasts 16 and skeletal myoblasts. 14,15,19 In vascular graft applications, topography driven from the size distribution of nanofibers influences the platelets adhesion on membranes and the blood compatibility.…”
Section: Introductionmentioning
confidence: 99%